“Publish or Perish”: The Indian Legal Academicians’ Dilemma of Prioritizing Research vs Teaching - Das, Shruti; Sharma, Deepshikha (UI Scholars Hub, 2023)
Research and Publication has been one of the key indicators of success for an academician. The term “publish or perish” came up with the connotation to understand the pressure academicians goes through for publication of research papers. In recent years, from Indian academic industry perspective, research has been one of the core criteria for promotion and evaluations. University Grants Commission (UGC), the regulatory body for Higher Education in India has made it mandatory to have a doctorate and some research publications to be eligible as an Associate Professor, though the proposed change in the regulation demands doctorate degree as a mandatory criterion to be eligible as an Assistant Professors in Indian Universities. National Assessment and Accreditation Council (NAAC), an autonomous institution of UGC assures quality of an educational institution recognised by UGC, has seven key indicators for giving ranks in the institutions. Institutions not meeting the minimum criteria can be derecognised and barred from conferring degrees. The highest scoring amongst all indicators are research, innovations and extensions and the teaching- learning and evaluation being the second priority. Evidently to get better ranking and thrive in the competition of education impartment, there is more emphasis on research publications. There are various reasons for emphasising on research for improvement of teaching and also contrary opinions. The corelation of evaluation of academicians against the criteria of research publication has proven to risk academic research integrity. The research has analysed documents of UGC and NAAC as also examined promotion and reward policies of five (5) central & state universities in India and five (5) private universities in India who cater to legal education. Twenty (20) Assistant Professors from various law schools in India have been interviewed to obtain insight between individual priorities of teaching and research. The result of the empirical study showed almost 70% of the academicians prioritize research over teaching. The reward system and database analysis also showed overprioritizing of research over teaching. This forces teachers to invest more time and energy for research than teaching their students. For teachers who try to provide equal attention to teaching and research are overburdened and evidently stressed out. The researchers propose some recommendations for Indian Higher education institutions to have a balance of both the responsibilities of an academician.